TIPIFICACIÓN DE LA PROPAGACIÓN MALICIOSA DEL VIH COMO MEDIDA DE PROTECCIÓN DE LOS DERECHOS FUNDAMENTALES DE LA PERSONA - SOTOMAYOR CAMARGO, JUAN TOMAS (2020)
To talk about intentional transmission of HIV is to refer to one more way of exercising violence. It has to do with the person who knows your diagnosis and does not take the necessary precautions to prevent transmission. We observe the deficiency in our Criminal Code that is not specifically typified the intentional programming of this virus, being only considered as an injury but not as a crime. In other countries such as Uganda, the "intentional and stubborn transmission" of the HIV virus has become a crime. KEYWORDS: HIV, SEXUAL TRANSMISSION